Combined oral contraceptives increase high-sensitivity C-reactive protein but not haptoglobin in female athletes - Cauci, S.; Francescato, M. P.; Curcio, F. (Sports Medicine, 2017)
Background: No studies have examined the effects of oral hormonal contraception on chronic low-grade inflammation as assessed by stratified levels of high-sensitivity C-reactive protein (hsCRP) in athletes. We explored the impact of combined oral contraceptives (OCs) on serum hsCRP, haptoglobin, triglycerides and cholesterol in white female athletes. Methods: Italian sportswomen (n = 205; mean age 24 ± 5.3 years; body mass index 21 ± 2.2 kg m-2; sport activity 8.7 ± 3.65 h week-1) were analyzed according to OC use. Results: Progressive hsCRP levels were evaluated in OC users (n = 53) compared to non-OC users (n = 152). Levels of hsCRP from 3.0 to <10.0 mg L-1 (at high risk of future cardiovascular events) were found in 26.4 % (14/53) of OC users and only in 2.6 % (4/153) of non-OC users (OR = 13.3, 95 % CI 4.14-42.6, P < 0.001). Risky hsCRP levels =1.0 mg L-1 were found in 62.3 % of OC users versus 13.2 % non-OC users (OR = 10.9, 95 % CI 5.26-22.5, P < 0.001). Protective hsCRP levels (<0.5 mg L-1) were found in 17.0 % of OC users and in 64.5 % of non-OC users (OR = 0.11, 95 % CI 0.05-0.25, P < 0.001). OC use increased serum triglycerides (P < 0.001), total cholesterol (P = 0.027) and HDL cholesterol (P = 0.018), whereas haptoglobin was unaffected. Hours of exercise week-1 had a mild inverse association with hsCRP (P = 0.048) in non-OC users only. Conclusions: OC use markedly elevated chronic low-grade inflammation in athletes, which could predispose to a higher inflammatory response to physical stress and elevate cardiovascular risk. Physical activity without OC use seemed to favor low hsCRP. Further research is needed to extend our results and to elucidate the potential effects on athletic performance of chronically elevated hsCRP. Our findings would be useful for sport physicians interpreting blood tests in athletes.